2021
DOI: 10.2217/fon-2020-1193
|View full text |Cite
|
Sign up to set email alerts
|

Risk Tolerance in Adjuvant and Metastatic Melanoma Settings: A Patient Perspective Study Using the Threshold Technique

Abstract: Background: Adverse events (e.g., pyrexia) may affect treatment patterns and adherence. This study explored pyrexia risk tolerance among melanoma patients when treatment benefit is unknown versus known. Materials & methods: US respondents with stage III (n = 100) or stage III unresectable/stage IV melanoma (n = 125) chose between hypothetical melanoma treatments, defined by reoccurrence/progression-free survival and pyrexia risk, one resembling standard-of-care and one resembling dabrafenib + trametinib. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Interestingly, patients were more willing to accept TT-associated pyrexia if the drug efficacy and, therefore, their outcome benefit is known (Mansfield et al 2021 ), physicians should focus on precise and adequate information in the informed consent process.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients were more willing to accept TT-associated pyrexia if the drug efficacy and, therefore, their outcome benefit is known (Mansfield et al 2021 ), physicians should focus on precise and adequate information in the informed consent process.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the scenarios with exception of scenarios 3, 7, and 11 (severe side effects; all < 5%) and scenario 12 (melanoma relapse, 17%) were rated as completely unacceptable (VAS = 0) by less than 1% of the patients, showing the immense willingness of German and Swiss patients to tolerate treatment-related side effects. Interestingly, a study by Mansfield et al showed that patients were more willing to accept TT-associated pyrexia if the drug efficacy and, therefore, their outcome benefit is known (Mansfield et al 2021 ). Patients in the adjuvant setting were more willing to accept pyrexia compared to patients with advanced melanoma (Mansfield et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study by Mansfield et al showed that patients were more willing to accept TT-associated pyrexia if the drug efficacy and, therefore, their outcome benefit is known (Mansfield et al 2021 ). Patients in the adjuvant setting were more willing to accept pyrexia compared to patients with advanced melanoma (Mansfield et al 2021 ). This demonstrates that it is crucial to explain thoroughly the potential treatment benefit in order to achieve the optimal patient willingness to accept adjuvant treatment of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous research has shown that patients prefer treatment alternatives with less risk for cancer recurrence over treatments with fewer side effects: Mansfield et al reported that a vast majority of patients with nonmetastatic skin melanoma preferred a theoretical intervention with 63% risk for pyrexia and 12% risk of recurrence over an intervention with 0% risk for pyrexia but with 44% risk of recurrence. 24 This could be likened to the selection of primary plaque brachytherapy or primary enucleation, where most patients might prefer the latter even though it has greater consequences for vision and cosmetic appearance, if the risk for recurrence becomes too high with the former. It is therefore questionable if primary plaque brachytherapy is a suitable procedure for patients in the high-risk class.…”
Section: Discussionmentioning
confidence: 99%